Mongrel nation diasporic culture and the making of postcolonial Britain - Dawson, Ashley 1965- (The University of Michigan Press, 2007)
Mongrel Nation surveys the history of the United Kingdom's African, Asian, and Caribbean populations from 1948 to the present, working at the juncture of cultural studies, literary criticism, and postcolonial theory. Ashley Dawson argues that during the past fifty years Asian and black intellectuals from Sam Selvon to Zadie Smith have continually challenged the United Kingdom's exclusionary definitions of citizenship, using innovative forms of cultural expression to reconfigure definitions of belonging in the postcolonial age. By examining popular culture and exploring topics such as the nexus of race and gender, the growth of transnational politics, and the clash between first- and second-generation immigrants, Dawson broadens and enlivens the field of postcolonial studies
Keywords: Commonwealth; Geschichte 1945-2006; Geschichte 1945-2005; Diversité culturelle; Groupes ethniques; Immigrants dans la littérature; Littérature anglaise; Littérature du Commonwealth (anglaise); Littérature et société; Postcolonialisme dans la littérature; Postcolonialisme; Commonwealth literature (English); Cultural pluralism; English literature; Ethnic groups; Immigrants in literature; LITERARY CRITICISM; Literature and society; Minorities in literature; Postcolonialism in literature; Postcolonialism; Commonwealth literature (English) -- History and criticism; Cultural pluralism -- Great Britain; English literature -- Minority authors -- History and criticism; English literature -- 20th century -- History and criticism; Ethnic groups -- Great Britain -- History -- 20th century; Literature and society -- Great Britain -- History -- 20th century; Postcolonialism -- Great Britain; Schwarze -- Motiv; Schwarze; Englisch; Literatur; Großbritannien; Literature; 1900-1999; Great Britain; Electronic books; Criticism, interpretation, etc; History; Aufsatzsammlung